Use of T1 relaxation time in rotating frame (T1ρ) and apparent diffusion coefficient to estimate cerebral stroke evolution. Issue 5 (15th February 2018) - Tan, Yuefa; Xu, Jun; Chen, Ruiying; Chen, Bin; Xu, Juan; Ren, Daokun; Chan, Queenie; Mei, Yingjie; Wu, Yuankui; Xu, Yikai
Abstract : Background: The major factor for the appropriate treatment strategies for ischemia patients is its onset timing. Purpose/Hypothesis: To study to evaluate the diagnostic accuracy of T1 relaxation time in a rotating frame (T1 ρ) and apparent diffusion coefficient (ADC) from MRI to estimate ischemia stages. Study Type: Prospective. Population/Subjects/Phantom/Specimen/Animal Model: In all, 73 patients (49 males, aged 29–78 years and 24 females, aged 22–94 years) with ischemia were prospectively imaged with T1 ρ and diffusion MRI during the postischemic period. Field Strength/Sequence: 3T/T1 ρ and diffusion‐weighted imaging (DWI). Assessment: Ischemic parenchyma included tissue with elevated signal areas on DWI and correlative hypointense areas on ADC maps. Statistical Tests: The sensitivity of variables to ischemia time was quantified by analyzing the respective correlations of these values with onset time. Results: ΔT1 ρ (ipsilateral‐contralateral differences in T1 ρ) (R 2  = 0.956) and T1 ρipsi (ipsilateral ischemia T1 ρ values) (R 2  = 0.941) were elevated in all ischemic lesions; these values increased linearly as a function of time, unlike ΔADC (ipsilateral‐contralateral differences in ADC) (R 2  = –0.410) and ADCipsi (ipsilateral ischemia ADC values) (R 2  = 0.550). ΔT1 ρ and T1 ρipsi were significantly different between all stages ( P  < 0.01), except the acute and hyperacute stages ( P  = 0.589 for ΔT1 ρ, P  = 0.290 for T1 ρipsi, respectively), but ΔADC and ADCipsi only between the late subacute and early subacute stages ( P  < 0.01) and the late subacute and chronic stages ( P  < 0.01). Data Conclusion: These data suggest that T1 ρ can provide estimates for the ischemic time in patients. T1 ρ has the potential to outperform diffusion for single‐timepoint examination because the T1 ρ change during strokes is positive and linear. If patients with suspected stroke are scanned by MRI within the appropriate timeframe, T1 ρ may provide tools for evaluating stroke onset, potentially aiding in treatment strategies. Level of Evidence: 4 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:1247–1254.